To the anniversary of the Department of Nonlinear Physics of Saratov State University - Beginin, Evgeny; Morozova, Maria; Savin, Aleksej (Luchshie medit͡s︡inskie t͡s︡entry Moskvy, 2024)
2023 marks the 25th anniversary of the formation of the Department of Nonlinear Physics of Saratov State University. The department has developed and implements training programs on the general course of physics, physics of nonlinear processes, physics of wave processes in magnetic fields and structures.